Insuficiencia respiratoria aguda - Gutiérrez Muñoz, Fernando R. (2010)
Basic respiratory function is gas exchange of oxygen and carbon dioxide, which implies a perfect balance and control between the components of the respiratory system. acute respiratory failure (ARF) is the inability of the respiratory system to fulfill its basic function, which is the gas exchange of oxygen and carbon dioxide.